2021
DOI: 10.3389/fendo.2021.657752
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition and Serum Anti-Müllerian Hormone Levels in Euthyroid Caucasian Women With Hashimoto Thyroiditis

Abstract: ObjectiveWomen with Hashimoto thyroiditis (HT) are characterized by increased incidence of infertility and disturbances in body composition. Serum anti-Müllerian hormone (AMH), which reflects functional ovarian reserve, is decreased in women with HT and it be related to body mass. The aim of the present study was to investigate the relation between serum levels of AMH and body composition in HT compared to control group.Patients and MethodsWe examined 85 euthyroid women: 39 subjects with HT and 46 control wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 44 publications
1
12
1
Order By: Relevance
“…The former finding could be linked to the time-related reduction in TV on L-T4 treatment [ 30 ], and the latter to genetic factors [ 23 ]. Only Adamska et al [ 20 ] reported TV in their study on AMH; they found no difference in TV between women with Hashimoto’s thyroiditis and control women of same median age of 26 years, the median value being 10 ml, which is only slightly higher than that found in our women (8 ml). This difference in TV could be explained by the difference in age-range, goitre control by means of L-T4 treatment, and regional differences in iodine intake.…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…The former finding could be linked to the time-related reduction in TV on L-T4 treatment [ 30 ], and the latter to genetic factors [ 23 ]. Only Adamska et al [ 20 ] reported TV in their study on AMH; they found no difference in TV between women with Hashimoto’s thyroiditis and control women of same median age of 26 years, the median value being 10 ml, which is only slightly higher than that found in our women (8 ml). This difference in TV could be explained by the difference in age-range, goitre control by means of L-T4 treatment, and regional differences in iodine intake.…”
Section: Discussioncontrasting
confidence: 82%
“…Finally, in women aged 20-40 years, Kucukler et al [ 27 ] reported a significant inverse correlation between AMH and age both in those with normal thyroid function and in those with newly diagnosed sub-clinical or overt thyroid dysfunction. By contrast, on evaluating AMH levels in women aged 18-35 years, Adamska et al [ 20 ] did not find any age-related changes in AMH in either 46 normal or 39 euthyroid TPOAb-positive women in this age-range.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations